ANALISIS KEBIASAAN SISWA DALAM BERMAIN GAME ONLINE KELAS VI DI SD - Dulastri Munthe; Antonius Remigius Abi; Jontra Jusat Pangaribuan; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study about students’ habits in playing online games at the elementary school level. The study used a qualitative method with a case study approach. The informants in the interview involved eight people, three students as the key informants that played online games, three parents, two friends who also played online games, and one teacher. To find out the students’ habits in playing online games, the researcher conducted direct observations and interviews. After obtaining the results of the interview, the researcher obtained the information that students who had a habit of playing online games by using the application of Free Fire game spent more time playing online games. The times that students play online games started from morning until noon and continued at night so that the time used in a day was 7 to 8 hours per day. The places where students played online games were a tavern or small shops with the facility of wifi, on the terrace of the house and in the house. Students’ habit of playing online games had a negative impact on themselves and their parents. Students who play online games with the application of Free Fire game did not divide their time to studying, because much time was spent playing online games with Free Fire. The students dared to lie to parents, opposed against parents, and stole money to top up internet quotas to continue playing the game of Free Fire.